Novel CGS hole transport layer for perovskite solar cells - Darmawan, Michael Putra (Nanyang Technological University, 2022)
Over the last one-decade perovskite solar cell has shown promising improvements in their efficiency. However, despite the tremendous potential, its stability has been a real challenge to overcome. Due to their better stability, the use of inorganic hole transport layers (HTLs) in perovskite solar cells (PSCs) has increased the hope for its commercialization. However, one of the main issues currently experienced for inorganic HTLs is the poor quality of the HTL/perovskite interface. This subsequently leads to inefficient charge extraction and transport, negatively affecting the power conversion efficiency (PCE), and the lifetime of the device. Sulfur based compounds have been shown to improve the interface quality and supplement the growth of perovskite film, which reduces interfacial recombination. This project used CuGaS2 (CGS) film as a hole transport layer in perovskite solar cells. The effects of indium and aluminium doping in CGS (In-CGS and Al-CGS) were investigated to improve CGS hole-transporting properties, which include valence band maximum (VBM) matching, conductivity and band gap. XRD and PL spectroscopy of the perovskite film grown on CGS-based HTLs indicated the presence of a better-quality perovskite film compared to the one deposited on FTO. Finally, it was observed that 10% indium doping improved the device efficiency of the CGS HTL based devices from 5.82 to 7.90%.